Baseline Levels of Serum Progesterone and the First Trimester Pregnancy Outcome in Women with Threatened Abortion: A Retrospective Cohort Study. (3rd March 2020) - Deng, Yongshi; Chen, Chi; Chen, Siyun; Mai, Guanyan; Liao, Xiuping; Tian, He; Liu, Wenli; Ji, Shuling; Liu, Ying; Gao, Jie; Luo, Songping
Abstract : Objective . The relationship between serum progesterone and the first trimester pregnancy outcome of threatened abortion is still controversial. Therefore, we aimed to further study the association between these two parameters. Methods . The present study is an observational retrospective cohort study. A total of 726 participants who had threatened abortion from a hospital in Guangdong, China, were included in this study from 17th August 2011 to 30th October 2018. The exposure variable and the outcome variable were serum progesterone measured at baseline and early pregnancy outcome, respectively. Covariates involved in this study included patients' basic demographics, obstetric history, and clinical information. Results . A negative association and a saturation effect were detected between serum progesterone and the first trimester pregnancy outcome. When progesterone <90.62 nmol/L, an increase in 1 nmol/L of serum progesterone was associated with 3% decrease of the risk of miscarriage (OR: 0.97, 95% CI: 0.95-0.98). Conclusion . There was a greater risk of abortion when the serum progesterone level was less than 90.62 nmol/L. Our findings can better assist the clinician in understanding patients' conditions and making medical decisions.